The Effects of Mode and Task Complexity on Second Language Production. Issue 2 (20th February 2017) - Vasylets, Olena; Gilabert, Roger; Manchón, Rosa M.
Abstract : Taking a psycholinguistic orientation within task‐based language teaching scholarship, this study investigated the effects of mode (oral vs. written) and task complexity on second language (L2) performance. The participants were 78 Catalan/Spanish learners of English as a foreign language. Half of the participants performed the simple and complex versions of an argumentative, instruction‐giving task orally, the other half did it in writing. The comparison of the participants' oral and written performance revealed that speakers produced more idea units but that writers achieved higher scores for subordination, mean length of analysis‐of‐speech units, lexical diversity, extended idea units, and time on task. As for the effects of task complexity, the participants' written production showed more variation between the complex and the simple versions of the task. These findings are interpreted in light of task modality effects in L2 learning and discussed in relation to task complexity theory and research.